Review of the world species of Spaniopus Walker, 1833 (Hymenoptera: Pteromalidae), with description of a new species from the Russian Far East - Tselikh, Ekaterina (Zootaxa, 2015)
The species of Spaniopus Walker, 1833 (Pteromalidae) are reviewed. A new species from the Russian Far East, S. belokobylskiji sp. nov., is described and illustrated. Redescriptions and illustrations of all available types of Spaniopus species are provided. A key for the identification of the twelve known species of Spaniopus is given. Five species, Spaniopus fulvicornis Bouček, S. japonicus Kamijo, S. nigriceps Kamijo, S. sasacolae Kamijo and S. varicornis Bouček are recorded from Russia for the first time.